Roles of the librarian in a research library in the digital era: challenges and the way forward (2013)
This article describes the roles of librarians in a research library, particularly in the digital era. Librarians’ roles vary from the custodian of resources to providers of a diverse nature of activities ranging from collection development, organization of knowledge, information services, preservation and conservation, and management. Librarians perform the aforementioned functions traditionally by using printed tools ranging from collection development tools (e.g., publishers’ catalogues, books in print, Ulrich, bibliography); cataloguing tools (e.g., classification schemes such as Library of Congress Classification [LCC] and Dewey Decimal Classification [DDC]); information services (e.g., bulletin, notice board, flyers); preservation and conservation (e.g., clean shelves, use of acid free boxes); and so forth. The traditional ways of performing these functions is being eroded by modern technology. This calls for changes in the products and services of research libraries to the research community served. These changes and the roles that librarians play are discussed in this article. Also enumerated are the challenges, such as dwindling budgets, capacity building, inadequate facilities, among others, of optimizing innovative ways of achieving more enhanced services. Some suggestions that could move the profession forward are also proffered